L'adaptation de chanson dans l'album ”Cœur vagabond” de Bïa. Une brise de Brésil - Abbrugiati, Perle (ATeM – Archiv für Textmusikforschung, 2019)
Perle Abbrugiati's article explores Coeur vagabond/Coraçao vagabundo, the fourth record by the French-Brazilian artist Bïa, released in 2006. The bilingual album comprises an equal number of Brazilian-Portuguese adaptations from French songs and French adaptations from Brazilian songs. The aim of the present article is to identify the strategies applied in the translation of songs. To this end, the article's author herself uses translation within the framework of a comparative approach, confronting Bïa's translations with her own literal translations (not suitable to be sung) of the original lyrics. The objective is not to trace 'mistranslations' but to point out in how many different and intricate ways a translation can be faithful while being creative, and in what way and to what degree the song translator may take the liberty of 're-semantisation'.
Keywords: Chanson; traduction

“Portrait en Noir et Blanc”: Chico Buarque em francês por Bïa Krieger [“Portrait en Noir et Blanc”: Chico Buarque en français par Bïa Krieger] - Cassiano, Raissa Conde (Tradução em Revista, 2019)

Keyboard Fantasies: The Beverly Glenn-Copeland Story - Dixon, Posy (Greenwich Entertainment et Modern Films, 2019)

Experiments in Cultural Diplomacy: Music as Mediation in Canadian-Brazilian Relations (1940s-1960s) - Fillion, Eric (Université Concordia, 2019)

Why Lhasa de Sela Matters - Goodman, Fred (University of Texas Press, 2019)

Musiques et diversité à Montréal. Un orchestre dans une communauté d’immigrants roumains et moldaves - LeBlanc, Sébastien; Sako, Hatouma; Fernando, Nathalie (Cahiers d’ethnomusicologie, 2019)
Au sein de la province du Québec, la majorité des immigrants choisissent de vivre à Montréal et y forment des communautés au sein desquelles leurs pratiques musicales du pays d’origine perdurent au-delà du processus migratoire. Depuis trois ans, notre équipe de recherche travaille à Montréal auprès de diverses communautés issues de l’immigration pour comprendre comment le musical participe au « Vivre ensemble ». Nous émettons l’hypothèse que la musique est pour les immigrants un outil pertinent d’intégration et de négociation identitaire afin de vivre au sein d’une société conviviale et d’y contribuer. La perspective comparative qui est la nôtre vise à faire ressortir ce qui est privilégié selon les cas de figures par les communautés elles-mêmes tant au sujet des répertoires musicaux que des processus de reconstruction identitaires à travers la musique. Dans cet article, nous présenterons nos observations au sujet de la communauté issue de l’immigration roumaine et moldave. Le groupe ainsi nommé est loin de représenter une homogénéité quelconque en dehors de l’origine qui est mentionnée sur les fiches de données produites par Statistiques Canada. Nous nous appuyons sur des exemples précis issus de nos travaux de terrain auprès de cette communauté afin de démontrer que nous avons affaire à un cosmopolitisme musical qui trouve pleinement sa place et son expression dans un tel contexte urbain.

« Cohérence d’une œuvre métissée » : extrait de thèse de doctorat (2007) - Makdissi-Warren, Katia (Circuit, 2019)

Katia Makdissi-Warren : étapes et œuvres marquantes - Pascal, Noémie (Circuit, 2019)

L’univers de Katia Makdissi-Warren (un diagramme) - Pascal, Noémie (Circuit, 2019)

The Expression of the Tragic in the Chamber Cantata Dați-Mi Lampa Lui Aladin [Give Me Aladdin's Lamp] by Dora Cojocaru - Seraz, Roxana Maria (Musicology Papers, 2019)
Dora Cojocaru is recognized as an outstanding representative of the Cluj school of composition, but also as a strong voice in Romanian musicology. While her musicological output includes books, studies, articles, radio programs, conference papers, master classes and scientific communication sessions, her most important contribution remains the book entitled Creația lui Gyӧrgy Ligeti în contextul stilistic al secolului XX [Gyӧrgy Ligeti's Work in the Stylistic Context of the Twentieth Century], which was the first book about Ligeti that appeared in the Romanian musicological landscape. Dora Cojocaru’s compositional portrait can be drawn by following the language characteristics and compositional devices used in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. The composer’s work is characterised by a propensity for chamber music. The composer confesses that it is also a consequence of the fact that this genre comes with a plethora of expressive possibilities. In terms of the musical language used by the composer, its first characteristic is the concern to avoid repetition in expression and the variation of an already used musical material. This is strikingly evident in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. Another peculiarity is the construction based on a developmental discourse, while a third characteristic is the frequent construction of the discourse based on an economy of means and on a musical material consisting of only a few notes. In the case of this cantata, it is essential to note the historical context, which is closely linked to the symbolic title suggesting the composer’s desperate desire to bring her brother back to life, although she is aware that this is only possible by magic. The composer’s choice of lyrics is derived from the fact that Trakl’s and Rilke’s texts allude to the theme of death, which is one of the frequent themes of late Expressionism, and are therefore pervaded by a tragic note, in tune with the composer’s musical intentions. If we follow the text-music relationship, we notice some extremely significant moments, in which music creates sonic images that are suggestive of the message of the text.

Création contemporaine et partage des traditions : à la rencontre de Katia Makdissi-Warren - Tremblay, Vicky (Circuit : musiques contemporaines, 2019)
Un article de la revue Circuit, diffusée par la plateforme Érudit.